2015
DOI: 10.1089/ars.2014.6090
|View full text |Cite
|
Sign up to set email alerts
|

Facioscapulohumeral Muscular Dystrophy As a Model for Epigenetic Regulation and Disease

Abstract: Significance: Aberrant epigenetic regulation is an integral aspect of many diseases and complex disorders. Facioscapulohumeral muscular dystrophy (FSHD), a progressive myopathy that afflicts individuals of all ages, is caused by disrupted genetic and epigenetic regulation of a macrosatellite repeat. FSHD provides a powerful model to investigate disease-relevant epigenetic modifiers and general mechanisms of epigenetic regulation that govern gene expression. Recent Advances: In the context of a genetically perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 179 publications
(304 reference statements)
1
59
2
Order By: Relevance
“…A.2) and found that the 3 healthy LCLs with contracted 4qB alleles displayed FSHD1-like levels of DNA hypomethylation (GM16349, Q1=7.1%; GM16350, Q1=0.0%; GM16352, Q1=0.0%) as compared with the non-contracted 4qB alleles with healthy levels of DNA methylation. This data supports the hypothesis that the physical removal of heterochromatin at D4Z4 arrays causes the epigenetic disruption in FSHD1 [15, 26, 28, 57]. In addition, this data provides further support for the unifying model for FSHD [23], again confirming that a 4q35 D4Z4 contraction alone is not causal for FSHD, but requires a permissive 4qA subtelomere in cis to cause disease [39].…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…A.2) and found that the 3 healthy LCLs with contracted 4qB alleles displayed FSHD1-like levels of DNA hypomethylation (GM16349, Q1=7.1%; GM16350, Q1=0.0%; GM16352, Q1=0.0%) as compared with the non-contracted 4qB alleles with healthy levels of DNA methylation. This data supports the hypothesis that the physical removal of heterochromatin at D4Z4 arrays causes the epigenetic disruption in FSHD1 [15, 26, 28, 57]. In addition, this data provides further support for the unifying model for FSHD [23], again confirming that a 4q35 D4Z4 contraction alone is not causal for FSHD, but requires a permissive 4qA subtelomere in cis to cause disease [39].…”
Section: Resultssupporting
confidence: 78%
“…FSHD is ultimately caused by the disruption of epigenetic regulation governing the chromosome 4q35 D4Z4 macrosatellite array, combined with an FSHD-permissive 4q35 PAS, resulting in the pathogenic expression of the DUX4 gene [15, 26, 35, 57]. In FSHD1, the epigenetic disruption is caused by the loss of large regions of regulatory heterochromatin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consider Facioscapulohumeral Muscular Dystrophy (FSHD), the most prevalent myopathy affecting males and females of all ages (reviewed in [6]). In contrast to DMD, which is caused by the loss of a functional protein, FSHD is caused by the aberrant expression of a protein that is normally silent due to its extreme toxicity.…”
mentioning
confidence: 99%